Treatment of kidney clear cell carcinoma, lung adenocarcinoma and glioblastoma cell lines with hydrogels made of DNA nanostars. (27th January 2022) - Leo, Manuela; Lattuada, Enrico; Caprara, Debora; Salvatori, Luisa; Vecchione, Andrea; Sciortino, Francesco; Filetici, Patrizia; Stoppacciaro, Antonella
Abstract : Can DNA-GELs made of DNA nanostars help with the treatment of tumor cell lines? Abstract : Overcoming the systemic administration of chemotherapy to reduce drug toxicity and the application of personalised medicine are two of the major challenges in the treatment of cancer. To this aim, efforts are focused on finding novel nanomaterials for the targeted administration of drugs and bioactive molecules in the tumor sites. DNA-based hydrogels are promising candidates for these applications. However, while such materials are fairly known from a structural and physical standpoint, their effects on cell cultures are far less investigated. Here, we studied the biological response of three different cell lines (clear cell renal cell carcinoma 786-O, lung adenocarcinoma H1975 and glioblastoma U87MG) to the treatment with DNA-GEL – a DNA-based hydrogel composed of interacting DNA nanostars. Additionally, we investigated the structural modification of DNA-GELs under cell culture conditions. The results we collected show a cell type specificity of the response, with interesting implications for future applications.